The correlation of muscle thickness and pennation angle assessed by ultrasound with sarcopenia in elderly Chinese community dwellers - Zhu S (Dove Medical Press, 2019)
Siping Zhu,1,* Wei Lin,1,* Shu Chen,1,* Hanmei Qi,1 Siting Wang,2 Aisen Zhang,1 Jinmei Cai,1 Bing Lai,1 Yunlu Sheng,1 Guoxian Ding11Division of Geriatric Endocrinology, the First Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China; 2Division of Intensive Care Unit, Nanjing Jiangning Hospital, Nanjing, Jiangsu, People’s Republic of China*These authors contributed equally to this workBackground: Sarcopenia is typically defined as the loss of muscle mass, strength and low physical performance with aging. Ultrasound is a safe and easy method for evaluating muscle mass and quality by muscle thickness (MT) and pennation angle (PA), respectively. Although the positive correlations between MT and muscle mass and handgrip strength were observed, the relationship between MT, PA and physical performance remains unclear.Purpose: This study aimed to investigate the correlation of aforementioned ultrasound parameters with muscle mass, muscle strength and physical performance and explore the utility of ultrasound in predicting sarcopenia.Patients and methods: A total of 265 elderly Chinese community dwellers were included. MT of both forearm and lower leg as well as PA of gastrocnemius was assessed by ultrasound. Muscle mass was assessed by dual-energy X-ray absorptiometry. Muscle strength was measured by a Jamar hand dynamometer. Physical performance was assessed by the Short Physical Performance Battery (SPPB).Results: Anterior radial MT in men and regional MTs except posterior fibula in women were negatively correlated with the age. No significant correlation was observed between PA and the age in both genders. Posterior tibial MT and posterior fibula MT were positively correlated with the relative appendicular skeletal muscle mass in men and women, respectively. Anterior ulnar MT was positively correlated with grip strength in both genders. Moreover, gastrocnemius medialis PA showed a positive association with gait speed and SPPB in women but not in men.Conclusion: A combination of posterior fibula MT, anterior ulnar MT and gastrocnemius medialis PA measured by muscle ultrasound is helpful for the assessment of sarcopenia in Chinese elderly women. In addition, a combination of posterior tibial MT and anterior ulnar MT measured by muscle ultrasound is helpful for the assessment of sarcopenia in Chinese elderly men.Keywords: B-mode ultrasound, muscle thickness, pennation angle, muscle mass, muscle strength, physical performance